Inactivation of Patched1 in the Mouse Limb Has Novel Inhibitory Effects on the Chondrogenic Program - Bruce, Stephen J. (American Society for Biochemistry and Molecular Biology, 2010)
The bones of the vertebrate limb form by the process of endochondral ossification, whereby limb mesenchyme condenses to form an intermediate cartilage scaffold that is then replaced by bone. Although Indian hedgehog (IHH) is known to control hypertophic differentiation of chondrocytes during this process, the role of hedgehog signaling in the earlier stages of chondrogenesis is less clear. We have conditionally inactivated the hedgehog receptor Ptc1 in undifferentiated limb mesenchyme of the mouse limb using Prx1-Cre, thus inducing constitutively active ligand-independent hedgehog signaling. In addition to major patterning defects, we observed a marked disruption to the cartilage elements in the limbs of Prx1-Cre:Ptc1(c/c) embryos. Using an in vitro micromass culture system we show that this defect lies downstream of mesenchymal cell condensation and likely upstream of chondrocyte differentiation. Despite early increases in levels of chondrogenic genes, soon after mesenchymal condensation the stromal layer of Prx1-Cre:Ptc1(c/c)-derived micromass cultures is characterized by a loss of cell integrity, which is associated with increased cell death and a striking decrease in Alcian blue staining cartilage nodules. Furthermore, inhibition of the hedgehog pathway activation using cyclopamine was sufficient to essentially overcome this chondrogenic defect in both micromass and ex vivo explant assays of Prx1-Cre:Ptc1(c/c) limbs. These data demonstrate for the first time the inhibitory effect of cell autonomously activated hedgehog signaling on chondrogenesis, and stress the importance of PTC1 in maintaining strict control of signaling levels during this phase of skeletal development.